Isolasi dan optimasi produksi lipase alkali dari bakteri=Isolation and Optimation of Production of Alkaline Lipase from Bacteria - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The aim of this study was to obtain a bacterial lipase which was stable in alkaline condition and to find out optimum condition required for production of lipase and as preliminary study on a decrease of fat content of leather on tanning process using lipase produced. This study was carried out in four steps. 1. Isolation of bacteria producing lipase from chicken skin, goat skin and cow hide using a selected methum (pH 7.4±0.2) containing palm oil 0.50 % and spirit blue indicator 0.015 %. Incubation was at 37°C for 48 h. 2. pH stability test using phosphate and Tris-HCI buffers pH 7.5 to 11 (for 2 h, at 4°C). 3. Effect of growth conditions for lipase production from selected isolate (medium pH, temperature and time incubation). 4. Study on a decrease of a fat content of leather from goatskin. In this study twenty seven strains were isolated from the samples which showed a lipase activity. These were consisted of four isolated from chicken skin, nine from goat skin and 14 from cow hides. From these 27 strains, 10 strains were selected out which were higher lipase produceis, and were used for the next study. Of this strains, seven isolates were stable on alkaline conditions (8.0-11.0). From this data, strain KB-4 was selected out of the seven strains which was highest lipase producer and its enzyme was stable on alkaline conditions. Conditions for production of the enzyme from the strain KB-4 were optimized. The best conditions were: initial medium pH was adjusted to pH 7.5